INFLUENCER AND EVENT MARKETING: PURCHASING VIRTUAL ITEMS AT GAMER'S “MOBILE LEGEND” - Vania, Amelindha; Ni'amus Sya'ban, Asmul Zacky (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The growth of the business sector within the online gaming industry has experienced significant acceleration, prompting this sector to leverage the sale of virtual items as a form of currency within online games as a notable benefit. Mobile Legend is an immensely popular online game that has garnered significant attention and widespread appeal among individuals nationwide. The primary objective of this study was to examine the correlation between events and influencer marketing in their impact on purchasing decisions regarding virtual items in the renowned mobile game. This impact was further mediated by the motivation to make a purchase. The present study employs a quantitative research design, utilizing a purposive sampling technique to select participants. Data analysis uses a Structural Equation Model (SEM), and mediation testing is performed through bootstrapping. The findings of this study suggest that event marketing has a minimal impact on the purchasing decisions of virtual mobile legend items. Additionally, the mediating role of motivation between event marketing and purchasing decisions was not observed. This research highlights the significant impact of influencer marketing and purchases motivation on enhancing purchasing decisions for virtual items in the mobile legend game. Motivation plays a significant role in establishing a connection between influencer marketing and the decision-making process regarding purchasing virtual items in Mobile Legends. Subsequent investigations may delve deeper into the impact of influencer marketing on the augmentation of purchasing behavior within the realm of online gaming.